Penyelenggaraan Hak Absolut Negara atas Tanah dalam Pembebasan Tanah untuk Kepentingan Umum - Fathol Bari (Lembaga Pengembangan Kinerja Dosen, 2024)
One of the development efforts within the national development framework, the government/government agencies/institutions at every level carry out development authority for the Public Interest. Based on the concept of the State's Right to Control, the Government, on behalf of the Land State, has the absolute right to regulate, determine and determine land rights for the sake of realizing the welfare of the people. On the other hand, the government has an interest in acquiring land for the public interest. In this research, a juridical study was carried out on what is the state's right to control land in land acquisition for public purposes? And what is the government's authority to acquire land for public purposes? The aim of this research is to determine the state's right to control land for the public interest and to find out what the government's authority is in acquiring land for the public interest. The method used in this research is the Normative Juridical method, namely comprehensively reviewing the legal aspects of statutory provisions related to the settlement of compensation for land acquisition for the public interest. In this research, it was found that the State is only limited to regulating, determining and determining the allocation of land rights, and in procuring land for the public interest, the government or agencies using land as development objects are obliged to provide compensation in accordance with the value determined by the assessment team.